Adipocytokines in Non-functional Adrenal Incidentalomas and Relation with Insulin Resistance Parameters - Akkus, Gamze; Evran, Mehtap; Sert, Murat; Tetiker, Tamer (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Objective: Adrenal incidentalomas are diagnosed incidentally during radiological screenings and require endocrinological investigations for hormonal activity and malignancy. In certain studies, it has been reported that non-functional incidentalomas can be associated with high adipocytokines levels affecting the insulin resistance just like the adipose tissue with metabolic syndrome. Here, we studied serum adipocytokine levels including leptin, resistin, visfatin, omentin 1 and adiponectin in subjects with non-functional adrenal incidentaloma. Methods: Seventy-seven (77) patients (Female 57; Male 20) with non-functional adrenal incidentaloma (NFAI) were enrolled in the study. All patients’ past medical history, physical examination including Body Mass Index (BMI) and waist circumference were performed. The patients’ demographic, radiologic, hormonal and biochemical parameters were recorded. To compare the parameters, a control group (CG) (n=30) was formed from healthy volunteers. Both groups were matched for age, gender, waist circumference and BMI. Serum adipocytokines including leptin, resistin, visfatin, omentin 1 and adiponectin were measured quantitatively by ELISA. Fasting plasma glucose, insulin, sodium, potassium, cortisol, adrenocorticotropic hormone (ACTH), lipid profiles, and dehidroepiandrostenedion sulphate (DHEAS) were measured. Results: Mean age of the patients was 52.2±10.4 years. BMI and waist circumference of NFAI patients were 26.2±3.28 kg/m2 and 90.2 ±7.5cm, respectively. The mean age of the control group was 48.0±8.16. BMI and waist circumference values for the control group were 25.3±3.5 kg/m2 and 88.3±9.6 cm, respectively. When both groups were compared for age, gender, BMI and waist circumference were non-significant (p>0.05). Serum fasting insulin, total cholesterol, LDL, triglyceride levels of the NFAI group were significantly higher than CG (p<0.05). The insulin resistance index (HOMAIR) values of the NFAI subjects were found to be higher than CG (2.5±1.37, 1.1±0.3 p=0.00). Resistin level of NFAI group was also found to be higher than CG [286.6 ng/L vs. 197 ng/L; (P=0,00)], respectively. Leptin levels of NFAI were significantly higher than CG [441.1 ng/mL vs. 186.5 ng/mL; (P=0.00)] respectively. Adiponectin levels were significantly reduced in the NFAI group than in the CG [10.7 mg/L vs. 30.8 mg/L; (P=0.00)]. Comparision of visfatin and omentin levels was nonsignificant. Conclusion: In this study on subjects with non-functional adrenal incidentaloma, we found not only significantly decreased serum adiponectin levels but also increased leptin, resistin levels as well as dyslipidemia, hypertension and high insulin resistance index. All of which could affect insulin resistance and cardiovascular risk factors. The underlying mechanisms of these findings are unknown, hence further studies are needed.
Keywords: Adrenal incidentaloma